2022
DOI: 10.3389/fnut.2021.821824
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, Zinc, and Vitamin C: Potential Adjuvant Treatment for COVID-19 Patients

Abstract: The use of nutraceutical approaches may regulate the immune system, performing a potential strategy to contain the worst outcomes of COVID-19. We reviewed the current evidence surrounding nutritional/nutraceutical approaches for the therapy in patients with COVID-19. We searched the PubMed database to report randomized controlled trials (RCTs) and observational research that used melatonin, zinc, or vitamin C supplementation as an intervention for COVID-19 treatment. To date, we found only three concluded stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Of note, vitamin C will be highly effective among patients with deficiency (hypovitaminosis C) [ 53 ]. Despite a limited number of randomized clinical trials, and conflicting results from some, Borges et al found vitamin C as a likely beneficial adjuvant treatment for COVID-19 patients, particularly due to a reduction of inflammation and better oxygen functioning when vitamin C is provided [ 54 ]. The same conclusion is suggested by Vollbracht and Kraft, who stressed the role of vitamin C in Long-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, vitamin C will be highly effective among patients with deficiency (hypovitaminosis C) [ 53 ]. Despite a limited number of randomized clinical trials, and conflicting results from some, Borges et al found vitamin C as a likely beneficial adjuvant treatment for COVID-19 patients, particularly due to a reduction of inflammation and better oxygen functioning when vitamin C is provided [ 54 ]. The same conclusion is suggested by Vollbracht and Kraft, who stressed the role of vitamin C in Long-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of zinc increases in a diet containing protein, histidine, methionine, and citrate. However, some drugs ( Figure 1 ) and compounds/elements (e.g., phytic acid, cadmium, high doses of iron, and casein) lower the bioavailability of zinc by complexing with it [ 24 , 25 , 26 , 27 ]. Accordingly, it is imperative to identify compounds that increase or decrease the absorption of zinc during zinc therapy.…”
Section: Zincmentioning
confidence: 99%
“…After ingestion, zinc is released as Zn +2 ions and absorbed up to an extent of 33% in a normal healthy person, wherein a decrease in zinc absorption takes place with an increase in age. The zinc is transported to cells through transport proteins [ 24 , 25 ], where it demonstrates its biological effects, including antioxidant, immunostimulant, and antiviral effects ( Figure 1 ). Zinc deficiency can cause many effects, including growth hindrance, delayed sexual development, skin problems, diarrhea, alopecia, decreased appetite, osteoporosis, and increased susceptibility to viral infections.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, zinc therapy has been shown to reduce inflammatory cytokines (IL-1 and IL-6), enhancing type-I IFN response [ 37 ]. Hence, using zinc supplementation along with other therapeutic regimens can be proven as a more effective strategy to combat viral infections like SARS-CoV-2 [ 23 , 38 ].…”
Section: Immunomodulatory Effects Of Zincmentioning
confidence: 99%